Case Study : Shegak / Aliah Wahidah Saharudin - Saharudin, Aliah Wahidah (2021)
Regarding to fulfil Fundamental of entrepreneurship (ENT300) course requirement, I need to carry out a case study .In this case study, I need to collect all information about a company to complete the task. The company that has been choose for this case study is a SHEgak This company sell variety kinds of scarfs and hair bands.To know more about this company I interview the owner Miss Ayu Nadhirah.The interview went well and I has successfully gather a lot of information regarding this company.For example ,the background of the business, organizational structure and about the products that the company sell. On top of that I also get to analysis the entrepreuneur characteristic that Miss Ayu have to control her business. This case study also requires the I to conduct an analysis that allows the me to perform an observation form of analysis that seeks to point out the Personal Entrepreneurial Competencies (PECs) in Entrepreneurship that exist in this selected entrepreneur. The researcher has found some points of PECs that describe the selected entrepreneurs as part of observation and analysis made by the researcher that can be referenced in this case study